The effect of credit rating announcements on covered bond returns : evidence from covered bonds issued by the three largest banks in Iceland - Hörður Guðmundsson 1995- (2020)
The purpose of this thesis is to examine how issuer credit rating announcements affect returns of covered bonds issued by the three largest banks in Iceland. The matching portfolio model is used to determine abnormal returns, which are calculated as the difference between daily covered bond returns and matching government bond index returns. Abnormal returns and cumulative abnormal returns associated with rating upgrades and affirmations are analyzed over a 21-day event window. The research is limited to the period of 2014 through 2018. The full sample includes seventeen rating announcement dates and 26 covered bonds. Findings show that announcement effects exist for rating affirmations and rating upgrades. The results suggest that rating agencies convey some new information to market participants. The results contribute to the discussion of market efficiency in Iceland and to the literature that analyzes bond markets in small open economies.